Development and validation of the measure of initial attraction- Short Interest Scale (MIA-I) - Rodrigues,David (2015)
Unilateral initial attraction (UIA) is a positive affective reaction following a unilateral perception of an unknown target, defining the first stage in developing a new interpersonal relationship. Although little attention is given to this construct, literature suggests it has a physiological activation component as well as an interpersonal interest component. However, this interest component emerges as necessary to willingly approach another person and eventually initiate interaction. Based on these evidences, we developed and validated the Measure of Initial Attraction - Interest Short Scale (MIA-I) in a sample of Portuguese-speaking individuals (Study 1, N = 544). Results suggest the MIA-I is a valid and reliable instrument (Study 1; Study 2a), and show its capacity to discriminate UIA across different relationships (Study 1) and to differentiate UIA from passion and love (Study 1). Towards an unknown target, the MIA-I also distinguished UIA from liking (Study 2b). These results show that the MIA-I assesses a specific construct, differentiated from liking, passion and love, and suggest its importance to understand the UIA phenomenon.